Collision of solid particles and solid surface - Goh, Shawn Kian Liang (2015)
Spraying process can be categorized into two different groups, cold spraying and warm spraying. In both processes, particles were accelerated by high speed gas jets to very high velocity in the range of 500m/s to 1000m/s. At such high velocity, metal particles which were in the form of powders adhere onto the targeted surface, forming strong bonds and eventually forms a coating on the surface. Cold spraying and warm spraying differs mainly by the temperature of the powder particles that were accelerated. For cold spraying, powder particles were unheated initially and impacts the surface with a temperature relatively lower than that of the warm spraying. As the name implies, warm spraying pre-heats the powder particles to a temperature below the melting point of the powder material in the barrel section, before travelling and impacting the surface. Warm spraying was generally developed after the cold spraying process, to decrease the critical velocity needed for adhesion. This consequently reduces the amount of combustion energy needed to reach the high velocity achieved in cold spraying. Both spraying processes were primarily used for coatings and repair in many manufacturing industries, including aerospace and military. Spraying processes were able to produce surface coating from a wide range of materials, which include metals and alloys to metal-based composites. However, due to the increasing demand and expectations from various industries, higher deposition efficiency and stronger coating structures were required for better performance and longer life span of the product. Furthermore, the study of the bonding mechanism achieved during high velocity impact was limited, even though they were of great interest. Therefore, this report focuses on studying the collision of particles at high velocity onto a solid substrate, in order to have a better understanding of the transfer of kinetic energy, deformations and possible adhesion criteria. Several experiments were conducted in this report. First, an electromagnetic coil gun was created to mimic the high velocity impact of the spraying process. Further improvements were made to gradually improve the velocity up till visible physical deformations were seen. Analysis was done on the impact process, with the use of a high speed camera to calculate the velocity achieved during and after the impact. Finally, surface scans were done on the substrate after impact with the help of the Confocal Imaging Profilometer, to measure the surface deformation and eventually the transfer of kinetic energy during the process. At high velocity impact, a significant amount of kinetic energy was transferred into deformation energy, when comparing the rebound velocity to the initial impact velocity, given by the coefficient of restitution. As the velocity of the particle increases, further transfer of the kinetic energy was converted into deformation energy, and the coefficient of restitution reaches zero, implying fully inelastic collision and therefore adhesion onto surface. Further work improvements includes ways to greatly increase the velocity of the particle, to reach its critical velocity for adhesion. Heating of the particle below its melting point could also be performed. With comparison to the warm spraying process, chances of adhesion could be increased and possibly to reduce the critical velocity required, for better studies of adhesion and deformation.